Medindo a eficácia dos professores: o uso de modelos de valor agregado para estimar o efeito do professor sobre o desempenho dos alunos - Moriconi, Gabriela Miranda (2012)
Given the importante of teachers to the educational process and availability of data for estimating measures of teacher effectiveness, understood as the ability to produce results in terms of student learning, this study sought to apply a value-added model to estimate and analyse the effectiveness of a sample of teachers who taught fourth grade in São Paulo’s municipal schools. We obtained evidence that variation in teacher effectiveness explains about 9% of the variation in students scores from the analysed sample, less than the variation in student background variables, aorund 15%, but more than variation in school variables, around 5%. For estimating teacher individual effects, results indicate that an increase of one standard-deviation in teacher effects would lead to a minimum increase of 0,062 standard deviation on student scores on Portuguese and 0,049 standard deviation on Mathematics, which represent 2,79 points in Portuguese and 2,20 points in Mathematics. In the analysis of factors associated to the teacher effects were found positive associations between the following variables and teacher effects: time devoted to teaching job out of the school, how often the teacher asks homework, and use of Learning and Support Workbooks. The analysis of reliability and stability of estimated teacher effect measurements indicate that this data have a limited capacity to support recommendations regarding personnel policies, but allow to identify that about 13% of the teachers had different effects from the estimated average. Given this distinction, these teachers are the ideal target to future research on their teaching practices, especially on the factors for which we observed a positive association with the estimated teacher effects.